2017
DOI: 10.1038/cr.2017.122
|View full text |Cite
|
Sign up to set email alerts
|

Structural and mechanistic insights into the biosynthesis of CDP-archaeol in membranes

Abstract: The divergence of archaea, bacteria and eukaryotes was a fundamental step in evolution. One marker of this event is a major difference in membrane lipid chemistry between these kingdoms. Whereas the membranes of bacteria and eukaryotes primarily consist of straight fatty acids ester-bonded to glycerol-3-phosphate, archaeal phospholipids consist of isoprenoid chains ether-bonded to glycerol-1-phosphate. Notably, the mechanisms underlying the biosynthesis of these lipids remain elusive. Here, we report the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…The two tunnels used by DGGGPase for substrate binding are similar to those of the CarS enzyme, the downstream enzyme of DGGGP in CDP-archaeol biosynthesis, and its structural homolog, TmCdsA (Liu et al, 2014), a bacterial CDP-DAG synthase (PDB: 4q2e and 4q2g). Both CarS and TmCdsA require bulky hydrophobic tunnels to accommodate substrates with two lipid tails (Ren et al, 2017), but they are structurally distinct. Overall, our findings reveal that members of the UbiA superfamily have distinct mechanisms of substrate recognition despite their similar structural motifs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The two tunnels used by DGGGPase for substrate binding are similar to those of the CarS enzyme, the downstream enzyme of DGGGP in CDP-archaeol biosynthesis, and its structural homolog, TmCdsA (Liu et al, 2014), a bacterial CDP-DAG synthase (PDB: 4q2e and 4q2g). Both CarS and TmCdsA require bulky hydrophobic tunnels to accommodate substrates with two lipid tails (Ren et al, 2017), but they are structurally distinct. Overall, our findings reveal that members of the UbiA superfamily have distinct mechanisms of substrate recognition despite their similar structural motifs.…”
Section: Discussionmentioning
confidence: 99%
“…Membrane lipid strips were utilized as previously described (Dowler et al, 2002), and the detailed experimental procedures were as reported by Ren et al (2017). Briefly, 0.2 ml (0.005 mM) of synthesized lipids GGPP or GGGP was spotted onto Hybond-C extra membranes (GE Healthcare Life Sciences), and the membrane strips were dried using a hair dryer.…”
Section: Resource Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the key step in phospholipid synthesis is the same in all three (Jain et al, 2014). The structure of the CarS of Aeropyrum pernix (ApCarS) comprises of five transmembrane helices and cytoplasmic loops which form a large charged cavity for CTP and the lipophilic substrate, DGGGP to bind (Ren et al, 2017). Part of the cavity is formed by two cytoplasmic loops, also contributing to substrate binding similar to TmCdsA (Figure 2A).…”
Section: Identification Of Prokaryotic and Eukaryotic Cds Enzymesmentioning
confidence: 99%
“…Cell membranes of most terrestrial organisms are glycerol phosphate phospholipids [1]. In Bacteria and Eukarya, they occur in glycerol-3-phosphate configuration, while Archaea use glycerol-1-phosphate to build their polar head groups [2]. It was shown that precursors of lipids like glycerol-1-phosphate can be formed abiotically by prebiotic chemistry by reductive homologation of hydrogen cyanide and some of its derivatives [3].…”
Section: Introductionmentioning
confidence: 99%